Penerapan metode mind mapping dalam meningkatkan motivasi siswa pada pembelajaran pasing bawah bola voli - Salsadilla, Ibry Leony; Nasution, Nana Suryana; Nurwansyah, Rhama (Jurnal Porkes, 2023)
The purpose of this study is to find out the application of the mind mapping method in increasing student motivation in learning volleyball underhand passing, where teachers still use conventional methods. The method used in this study uses classroom action research to solve problems that occur, efforts to increase student motivation in learning volleyball underfoot by using the mind mapping method. The population is 31 students. The stages which are divided into several steps starting from planning, action and observation in a cycle, the results of research on teacher activity cycle I amounted to 3.36% in the good category and increased in cycle II by 4.45% in the very good category. The first cycle of 51.7% increased in the second cycle of 80.6%, which means that classical learning mastery has been achieved. the results of student responses through a questionnaire that had been distributed as many as 10 student statement questions gave good response results. This means that the application of the mind mapping method to learning volleyball underhand passing to increase student motivation in this study is very suitable to be applied in Mts Asy-Syifa schools, Bekasi Regency.